Governance and Utilization of the Bode Watershed in Gorontalo: Public Perceptions and Sustainability Challenges - Saputra Widodo, Eka Reza; Irawan, Mohammad Bayu; Prasetyo, Mawardi Heru; Lihawa, Fitryane; Dunggio, Iswan (Universitas Andi Djemma Palopo, 2025)
The Bone Watershed (DAS Bone) in Gorontalo Province serves as a vital resource supporting agriculture, fisheries, and clean water supply. However, it faces significant challenges such as land conversion, deforestation, resource exploitation, and weak oversight of illegal mining activities. This study aims to evaluate community perceptions of the management and utilization of DAS Bone and to identify sustainability challenges. A mixed-method approach was applied, combining quantitative surveys using a Likert scale with qualitative in-depth interviews involving 100 respondents living in the watershed area. Findings reveal that most community members have a positive perception of the importance of watershed conservation and believe that environmental sustainability has been considered in current management efforts. Nonetheless, respondents also highlighted a lack of regular outreach and insufficient government supervision, particularly concerning gold and C-excavation mining. Economically, water and fisheries usage provide tangible benefits, whereas agriculture is seen as less supportive of livelihoods due to flood vulnerability. On the other hand, there is strong community support for renewable energy development, such as mini-hydro and psycho hydro technologies, due to their environmental friendliness and socio-economic benefits. This study recommends enhancing community involvement, integrated monitoring systems, and sustainable infrastructure and energy planning. The findings are expected to serve as a policy input for local governments to design more community-based and sustainable watershed management strategies.